Effect of pre artificial insemination administration of amoxicillin + cloxacillin on conception rate in normal and repeat breeding cross bred cattle - MAHTO, DINESH; SINGH, M P; SINGH, BALRAJ; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
A total number 6f 33 animals grouped under normal and repeat breeding category were treated with singledose amoxicillin+cloxacillin combinations. The amoxicillin + cloxacillin was infused intra-uterine 8-12 hrs preinsemination during estrous to evaluate the efficacy on the conception rate in normal and repeat breeder cows. In.normal animals the conception rate with pre A.I. treatment was 63.63 % as compared to 33.33 % for controlgroup. Similarly in repeat breeding cows, the conception rate was 60.00 with pre A.I. treatment as compared to16.66 % in control group. The differences were recorded to be non-significant.
Keywords: Repeat breeder; cross-bred cattle